Analysis of Dumpling House Msmes From The Perspective of Mc Kinsey 7s - Salim, Elizabeth Gina Mitayanny; Harianto, Eric (JIBEMA: Jurnal Ilmu Bisnis, Ekonomi, Manajemen, dan Akuntansi, 2024)
Small and Medium-sized Enterprises (MSMEs) play a significant role in Indonesia's economy, absorbing up to 97% of the workforce. Particularly, the food and beverage sector within MSMEs has shown substantial growth, indicating high potential in the industry. However, intense competition poses challenges, necessitating a competitive edge for sustained growth. This paper examines the case of Dumpling House, an MSME in the frozen food sector, which initially experienced rapid expansion but faced challenges due to the evolving business landscape. Using the McKinsey 7s framework, the internal analysis reveals areas for improvement in strategy, structure, system, shared values, skills, style, and staff. While Dumpling House demonstrates strengths in certain areas, such as product quality and employee camaraderie, there are evident gaps in strategic planning, leadership, and system optimization. The study suggests enhancing management insights, conducting regular evaluations, strengthening leadership roles, and addressing identified issues comprehensively to facilitate Dumpling House's continued growth and success.